Search for pair production of doubly charged Higgs bosons in the H(++)H(--)->mu(+)mu(+)mu(-)mu(-) final state - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Sosebee, M.; et al. (Amer Physical Soc, 2008)
We report the results of a search for pair production of doubly charged Higgs bosons via p (p) over bar -> H(++)H(--)X ->mu(+)mu(+)mu(-)mu(-)X at root s=1.96 TeV. We use a data set corresponding to an integrated luminosity of 1.1 fb(-1) collected from 2002 to 2006 by the D0 detector at the Fermilab Tevatron Collider. In the absence of an excess above the standard model background, lower mass limits of M(H(L)(+/-+/-))> 150 GeV/c(2) and M(H(R)(+/-+/-))> 127 GeV/c(2) at 95% C.L. are set, respectively, for left-handed and right-handed doubly charged Higgs bosons assuming a 100% branching ratio into muons.